Single Vesicle Assaying of SNARE-Synaptotagmin-Driven Fusion Reveals Fast and Slow Modes of Both Docking and Fusion and Intrasample Heterogeneity - Christensen, Sune M. (The Biophysical Society, 2011)
Lipid mixing between vesicles functionalized with SNAREs and the cytosolic C2AB domain of synaptotagmin-1 recapitulates the basic Ca(2+) dependence of neuronal exocytosis. However, in the conventional ensemble lipid mixing assays it is not possible to discriminate whether Ca(2+) accelerates the docking or the fusion of vesicles. Here we report a fluorescence microscopy-based assay to monitor SNARE-mediated docking and fusion of individual vesicle pairs. In situ measurement of the concentration of diffusing particles allowed us to quantify docking rates by a maximum-likelihood approach. This analysis showed that C2AB and Ca(2+) accelerate vesicle-vesicle docking with more than two orders of magnitude. Comparison of the measured docking rates with ensemble lipid mixing kinetics, however, suggests that in most cases bilayer fusion remains the rate-limiting step. Our single vesicle results show that only ∼60% of the vesicles dock and only ∼6% of docked vesicles fuse. Lipid mixing on single vesicles was fast (t(mix) < 1 s) while an ensemble assay revealed two slow mixing processes with t(mix) ∼ 1 min and t(mix) ∼ 20 min. The presence of several distinct docking and fusion pathways cannot be rationalized at this stage but may be related to intrasample heterogeneities, presumably in the form of lipid and/or protein composition.